This Study Examines The Quality Of Customer Service, Tellers, And Security Services The PT. Bank Sumut Pangururan Branch Ensures Customer Satisfaction - Grace Bertauli Tumanggor; Jamaluddin Jamaluddin; Flora Tambunan; Sondang Rouly Purba; Hendra Saputra (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to analyze the effect of customer service quality, teller, and security on customer satisfaction at PT. Bank Sumut, Pangururan Branch. We used a survey method with a questionnaire, selecting 55 bank customers as saturated samples. Regression techniques analyzed the collected data to determine the relationship between the studied variables. The results showed that the quality of customer service, teller, and security had a significant effect on customer satisfaction. Respondents stated that customer service, teller, and security provided friendly, responsive, and professional service that increased their level of satisfaction. We also found that specific factors like the ability to handle transactions quickly and accurately, willingness to help, and efforts to maintain security in the bank environment positively impact customer satisfaction. This study provides a deeper understanding of the importance of service quality in influencing customer perceptions of the bank. These findings have managerial implications, including the need to improve employee interpersonal skills training, improve systems and procedures to improve service efficiency, and ensure physical security and information provided to customers. In addition, banks can also use these findings as a basis for designing better development strategies to improve customer loyalty and satisfaction in the future.